Quasi-biennial oscillation in foF2 at the south crest of the equatorial anomaly - Mansilla, Gustavo Adolfo (2009)
The aim of this paper is to report some periodicities observed in the ionospheric parameter foF2 measured at Tucuman (26.9°S; 65.4°W), station placed near the southern crest of the equatorial anomaly. For that, monthly medians of foF2 at several hours of LT for the period 1958–1987 are used. The data are run with Fast Fourier Transform (FFT). Data gaps (∼4–5 months) are filled by means of linear interpolation. Several periodicities are present. Besides the solar cycle dominant dependence (∼11 years), semi-annual, annual, five years and quasi-biennial periodicities are also observed. A marked quasi-biennial periodicity is observed at daytime and nighttime hours being their greater amplitude at local noon and midnight. Different mechanisms or combined effects possibly cause them. It is suggested that the solar activity by means of extreme ultraviolet radiation (EUV), which present a quasi-biennial oscillation (QBO) and it is responsible for the ionization, could be the dominant mechanism for the diurnal quasi-biennial periodicity of foF2. At night, since the photoionization by extreme ultraviolet radiation is not significant and the F2 layer is lower than during daytime (∼100 km) other mechanism may be operative for the quasi-biennial periodicity observed. Possibly the stratospheric QBO contributes to the modulation of the observed behaviour in foF2 at night. This result is preliminary because it needs to be extended to other stations so as to extract definite conclusions. Moreover, we cannot dismiss the possibility of a combined effect of both these mechanisms mainly at daytime and/or QBO influence of geomagnetic parameters.